Targeted therapy for glioma using cyclic RGD-entrapped polyionic complex nanomicelles - Liu X (Dove Medical Press, 2012)
Xiaoying Liu,1* Wenguo Cui,2* Bo Li,1 Zhen Hong31Department of Neurology, Ruijin Hospital, 2School of Biomedical Engineering and Med-X Research Institute, Shanghai Jiao Tong University, 3Department of Neurology, Huashan Hospital, Medical College, Fudan University, Shanghai China*These authors contributed equally to this articleBackground: The purpose of this study was to test the efficacy of cyclic Arg-Gly-Asp (RGD) peptide conjugated with polyionic complex nanomicelles as targeted therapy for glioma.Methods: A stable cyclic RGD polyionic complex nanostructure, ie, a c(RGDfC) polyionic complex micelle, was synthesized and its biocompatibility with cultured neurons was assessed using a cell viability assay. Targeted binding to cultured glioma cells was evaluated by the CdTe quantum dot marking technique and a cell viability assay. The inhibitory effect of the nanomicelles against glioma cells was also evaluated, and their targeted migration into rat brain glioma cells and apoptotic effects were traced by the CdTe quantum dot marking and immunohistochemical staining.Results: c(RGDfC) polyionic complex micelles did not affect the growth of neurons but bonded selectively to and inhibited proliferation of glioma cells in vitro. When tested in vivo, the micelles migrated into glioma cells, inducing apoptosis in the rat brain.Conclusion: The c(RGDfC) polyionic complex micelle is an effective targeted therapy against glioma.Keywords: Arg-Gly-Asp, RGD, polyion complex, micelle, glioma, target therapy